Immunomodulatory effects of oral microbiota in the pathogenesis of rheumatoid arthritis - Yang, Yiming; Wang, Guanyuan; Song, Yongzhou; Ma, Jun; Liu, Aijing (Frontiers in Immunology, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent synovial inflammation, progressive cartilage and bone destruction, and resulting functional disability. Its pathogenesis is multifactorial, involving both genetic predisposition and environmental influences. In recent years, the interaction between the oral microbiota and RA has emerged as a prominent research focus. Dysbiosis of the oral microbiome, defined as an imbalance in microbial composition relative to a healthy state, accompanies disease onset and may further act as a trigger of systemic autoimmune responses. Specific virulence factors, including the peptidylarginine deiminase from Porphyromonas gingivalis and leukotoxin A from Aggregatibacter actinomycetemcomitans, promote excessive protein citrullination and anti-citrullinated protein antibody generation, thereby contributing to the loss of immune tolerance, particularly in genetically susceptible individuals. Moreover, the bidirectional relationship between RA and periodontitis highlights shared inflammatory pathways that contribute to both periodontal and joint tissue destruction. Potential mechanisms include bacteremia induced by routine oral activities, systemic dissemination of bacterial products, and colonization of oral microbiota in the gastrointestinal tract. Current evidence suggests that periodontal therapy may reduce systemic inflammatory markers and occasionally improve RA activity, although results remain inconsistent. In this review, we explored the potential mechanisms underlying the imbalance of the oral microbiota and its contribution to the onset and progression of RA, focusing on microbially induced citrullination, host genetic susceptibility, and common inflammatory pathways, while also discussing the impact of comprehensive periodontal management and lifestyle interventions on RA outcomes. Overall, these insights underscore the role of the oral microbiome in RA pathogenesis and suggest that addressing microbial dysbiosis through integrated therapeutic strategies may complement conventional care.